Nutrient Losses during Winter and Summer Storage of Separated and Unseparated Digested Cattle Slurry. Issue 4 (1st July 2017) - Perazzolo, Francesca; Mattachini, Gabriele; Riva, Elisabetta; Provolo, Giorgio
Abstract : Management factors affect nutrient loss during animal manure slurry storage in different ways. We conducted a pilot‐scale study to evaluate carbon (C) and nitrogen (N) losses from unseparated and digested dairy slurry during winter and summer storage. In addition to season, treatments included mechanical separation of digestate into liquid and solid fractions and bimonthly mixing. Chemical analyses were performed every 2 wk for the mixed materials and at the start and end of storage for unmixed materials. The parameters examined allowed us to estimate C and N losses and examine the factors that determine these losses as well as emission patterns. Gas measurements were done every 2 wk to determine the main forms in which gaseous losses occurred. To evaluate the effect of separation, measured losses and emissions of separated liquid and solid fractions were mathematically combined using the mass separation efficiency of the mechanical separator. Nutrient losses were mainly affected by climatic conditions. Losses of C (up to 23%) from unseparated, unmixed digestate and of N (38% from combined separated fractions and from unseparated digestate) were much greater in summer than in winter, when C and N losses were <7%. Mixing tended to significantly increase N losses ( P < 0.1) only in winter. Mechanical separation resulted in lower GHG emissions from combined separated fractions than from unseparated digestate. Results indicate that to maximize the fertilizer value of digested slurry, dairy farmers must carefully choose management practices, especially in summer. For separated digestates, practices should focus on storage of the liquid fraction, the major contributor of C and N losses (up to 64 and 90% of total losses, respectively) in summer. Moreover, management practices should limit NH3, the main form of N losses (up to 99.5%). Core Ideas: Season had the most significant effect on N and C losses during slurry storage. Mechanical separation did not significantly affect N and C losses. In summer, temperature caused losses of up to 38% of TKN and 23% of TOC from digested slurry. CO2 and NH3 were the predominant gaseous forms of C and N losses.